Digital Marketing and Social Media: A Review: Digital Marketing and Social Media - Ünvan, Yüksel Akay; Badlo, Yuliya (E-business technologies conference proceedings, 2021)
Nowadays it is not possible to foreseen future prospects of business and trade development without realizing the role and importance of platforms that thousands of people use on a daily basis, for both: producers and consumers. Social and digital marketing offers great opportunities for companies to increase their brand awareness and sales. The use of social media has changed customer behaviour and consequently the way companies do business. That is why it remains necessary to further analyse current state of the existing platforms that determines success of online marketing. It is proposed to overview current and future trends in this field. Obtained results state that the communication of the consumer with brands through social media has a positive effect on customer-based brand value. It is considered that it creates a strong connection between customers and the company.